Transformasi Tata Kelola Legislatif di Palembang Platform Legislasi Digital Terintegrasi - Muhammad Farhan; Sri Rahayu (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
Public information disclosure requires the Legal Documentation and Information Network (JDIH) to provide legal data services that are fast, accurate, and easily accessible. JDIH Palembang City, as a strategic instrument of governance, has a vision to realize integrated technology-based management. However, field observations identified significant operational challenges hindering the achievement of this vision. The main problems lie in the suboptimal archive digitization process, reliance on physical documents, and the risk of losing vital archive data. This research aims to address these problems by proposing a "product" in the form of an integrated digital legislation platform design. The research method used is Prototyping, which includes stages of needs identification, system design, and prototype development. The system design is modeled using Unified Modeling Language (UML) and Entity-Relationship Diagram (ERD). The results of this study are a system architecture and user interface prototypes (mockups) that integrate an Optical Character Recognition (OCR) module for digitization automation, centralized database management, and a full-text search feature. This proposed platform is expected to improve the efficiency of JDIH's internal workflow and optimize legal information services to the public.